Agroecological Practices as Contribution to the Sustainability of Agroecosystems. Case Study of Sumapaz Province - Albarracín-Zaidiza, Jorge Andrés; Fonseca-Carreño, Nelson Enrique; López-Vargas, Luis Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The sustainability assessment was carried out on 12 agroecosystems in the Sumapaz province in Cundinamarca, through the MESMIS methodology. The attributes evaluated were: productivity, reliability, adaptability, self-management, equity, stability, and resilience. The objective of the research is to identify strategies to improve the relationship between agroecosystems and agroecological practices and thus contribute to the sustainable preservation of production systems. The description of biophysical and socioeconomic variables was obtained from a review of secondary and primary sources: field checks, interviews, guided tours and social cartography. Agroecosystems were evaluated through 20 sustainability indicators, within the economic, social and environmental dimensions. The results show that they are "moderately sustainable", with positive rates ranging from 62 to 74%, due to the socioeconomic and productive conditions at the farm level, which are operated by family labor, which generates stability in terms of knowledge of the area, landscape, fertility, vegetation, water sources and vegetation expressions. In turn, agroecosystems are home to a great biodiversity and offer a wide range of benefits through ecosystems, which encourages the incorporation of agroecological practices, appropriate technologies for the use of renewable energy sources, contributes gradually to the achievement of food sovereignty, thus contributing to sustainability.